Hubungan Paritas Dengan Berat Badan Lahir Rendah (BBLR) - Elis Fatmawati; Dwi Retno Wati (IJMT : Indonesian Journal of Midwifery Today, 2021)
One of the indicators that determine a country's health status is the high and low number of the Infant Mortality Rate (IMR). Meanwhile, the incidence of Low Birth Weight (LBW) is one of the main determining factors that contribute to the Infant Mortality Rate (IMR). Many factors cause an increase in the number of IMR, one of which is parity. This study aims to determine the relationship between parity and low birth weight (LBW) in Cendrawasih Dobo Hospital, Aru Islands Regency.This study uses analytical research with a "retrospective" research design. The dependent variable is parity and the independent variable is LBW. The population in this study were all mothers who had LBW in Cendrawasih Dobo Hospital, Aru Islands Regency in 2020 as many as 42 mothers with LBW babies. Sampling using a total sampling technique. The study was conducted from July 1 to August 31, 2020, using secondary data, and analyzed using the Spearman Ranks statistical test.The results showed that almost half of the primiparous mothers gave birth to LBW babies, namely 15 babies (35.7%) and most of the multipara mothers gave birth to 22 LBW babies (52.4%). Based on the results of statistical tests using Spearman Rho with = 0.05) the value of count (0.470) > r table (0.257) then H1 is accepted, H0 is rejected, this means that there is a parity relationship with low birth weight (LBW).There were that not only high parity has the potential for LBW births, but even low parity has the potential to occur LBW births considering that there are many factors that can influence it, not only in terms of maternal parity. Health agencies can make efforts to prevent the occurrence of LBW by improving the quality of health services.